2018
DOI: 10.1016/j.envpol.2018.06.033
|View full text |Cite
|
Sign up to set email alerts
|

Microplastic hotspots in the Snake and Lower Columbia rivers: A journey from the Greater Yellowstone Ecosystem to the Pacific Ocean

Abstract: It is widely understood that microplastics (MPs) are ubiquitous in the marine environment yet less is known about MP abundance in freshwater rivers, particularly those of the western United States. This study documents MP pollution along the Snake River (∼1735 km) and from its confluence with the Columbia River to the Pacific Ocean. Grab and plankton net samples (mesh size 100 μm) were collected from the top 25 cm of surface water every 80.5 river km. MPs were identified if they met visual criteria and were ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(83 citation statements)
references
References 67 publications
1
72
2
Order By: Relevance
“…Concentrations of microplastics in water samples in the current study (0.44-9.70 particles/ m 3 ) are somewhat lower than a reported value for Brownlee Reservoir, another large reservoir in the western U.S. (13.7 particles/m 3 ; Snake River, Idaho/Oregon) [52]. Concentrations in water samples from the St. Croix and Mississippi Rivers (0.80-4.84 particles/m 3 ) [58], and from the much more urban Milwaukee Harbor and nearshore Lake Michigan (Wisconsin, USA; 0.21-5.23 particles/m 3 ) [60], were similar to those in the current study.…”
Section: Comparisons To Previous Studiescontrasting
confidence: 89%
See 1 more Smart Citation
“…Concentrations of microplastics in water samples in the current study (0.44-9.70 particles/ m 3 ) are somewhat lower than a reported value for Brownlee Reservoir, another large reservoir in the western U.S. (13.7 particles/m 3 ; Snake River, Idaho/Oregon) [52]. Concentrations in water samples from the St. Croix and Mississippi Rivers (0.80-4.84 particles/m 3 ) [58], and from the much more urban Milwaukee Harbor and nearshore Lake Michigan (Wisconsin, USA; 0.21-5.23 particles/m 3 ) [60], were similar to those in the current study.…”
Section: Comparisons To Previous Studiescontrasting
confidence: 89%
“…As with other studies of microplastics in freshwater [6,[50][51][52], in this study fibers were the most abundant microplastic type in all environmental compartments. Whereas fragments, films, and foams were more commonly found at locations with greater anthropogenic impact, fibers were ubiquitous across all locations.…”
Section: Plos Onesupporting
confidence: 86%
“…Dris et al () observed high microplastic concentrations in rivers (3–106 particles m −3 ), attributed to urban inputs such as treatment plant discharges. Kapp and Yeatman () reported microplastic concentrations in surface waters from the 1735 km Snake and 523 km lower Columbia Rivers (U.S.). They reported higher levels in areas adjacent to agricultural areas, possibly due to the use of biosolid fertilizers or plastic mulches.…”
Section: Microplastics In Freshwatersmentioning
confidence: 99%
“…An abundance of microfibers have been found in aquatic (freshwater and marine) and terrestrial environments worldwide [7][8][9][10][11]. Recent studies have observed microplastics, the majority of which were microfibers, in the French Pyrenees, the Italian Alps and in snow samples from the Arctic [12,13].…”
Section: Introductionmentioning
confidence: 99%